Cosmic Alignment and Social Shift: Reinterpreting Temple-Settlement Morphology in Central Java’s Living Sacred Landscape - Cinthyaningtyas Meytasari; Muhammad Sani Roychansyah (DIMENSI (Journal of Architecture and Built Environment), 2025)
This study examines the spatial differences between the cosmological orientations of Hindu-Buddhist temples and the evolving settlement patterns in Central Java. The focus of this research is on temples that are still considered sacred and actively used for religious rituals, such as Borobudur, Pawon, and Mendut (Buddhist), and Cetho and Sukuh (Hindu), which are closely linked to the settlement patterns of their surrounding areas. In comparison, the temples exhibit a symbolically directed orientation—generally toward the east, mountains, or sacred rivers—the surrounding settlement patterns now follow more pragmatic considerations such as accessibility, land economy, and tourism development. Methodologically, the study employs a qualitative-descriptive approach supported by Geographic Information System (GIS)-based spatial techniques using Google Earth. Azimuth analysis, overlay interpretation, and viewshed approximation are applied to examine temple orientations, settlement morphologies, and their symbolic relations to sacred topography. The concept of "social shift" is introduced to explain this gradual spatial deviation. This study strengthens the discourse on sacred landscape transformation. It offers an integrative heritage planning approach, taking into account the relationship between symbolic order and the spatial adaptation of modern society.